The Implementation of Self Instruction and Thought Stopping Group Counseling Techniques to Improve Victim Bullying Self Esteem (Universitas Negeri Semarang, 2018)
The aim of the study is to the test the effectiveness of group counseling by using self instruction and thought stopping techniques to improve self esteem of victim bullying students in the class VII of MTs Al Hikmah Proto Kedungwuni Pekalongan. The research method was experiment with randomized pretest-posttest control group design by involving 21 subjects purposively. The results showed that self instruction and thought stopping techniques were effective to improve self esteem of victim bullying students with different levels of group counseling effectiveness of self instruction technique was higher than thought stopping technique. Group counseling by using self instruction and thought stopping technique are effective to improve the self esteem of victim bullying students of MTs Al Hikmah Proto Kedungwuni Pekalongan